Persian nights [a novel] - Johnson, Diane (Knopf, 1987)
Chloe, a contented and unliberated wife and mother, follows her physician husband on a visit to Iran. When he is summoned home, she has no choice but to continue on alone.
Keywords: Frau; Americans -- Iran -- Fiction; Women -- Iran -- Fiction